Synthesis of Enantiomerically Pure 2-Heteroaromatic-Substituted 1,2-Amino Alcohols from Chiral tert-Butanesulfinyl Aldimines - Chen, Yantao; Goldberg, Frederick W.; Xiong, Jian; Wang, Shujun (Synthesis, 2015)
Nine R/S pairs of 2-heteroaromatic-substituted 1,2-amino alcohols were synthesized through 1,2-nucleophilic addition between chiral N-(tert-butylsulfinyl)imines and heteroaromatic carbanions. In most cases, the RS-isomer of N-(tert-butylsulfinyl)imines afforded the R amino alcohol from deprotection of the major diastereomer, and SS-imines afforded the S product. In general, this procedure allows for the preparation of a variety of enantiomeric pairs of 2-heteroaromatic-substituted 1,2-amino alcohols on a practical scale (>10 g) in two steps in good yields.
Keywords: amino alcohols; asymmetric synthesis; chiral auxiliaries; heterocycles; stereoselectivity